Testing BIOSEL-SR2020 to Reduce Physical-Chemical Contents in Faecal Sludge Treatment Installations in Puulonggida and Potential as An Organic Fertilizer Ingredient - Wibowo, Dwiprayogo; Sumarlin, Sumarlin; Aridan, Aridan; Herman, Suwardin; Murdi, Murdi; Ndibale, Wa; Eka Pratiwi, Yunita; Nurcayah, Nurcayah (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
To improve environmental health and address the issue of domestic fecal sludge waste, it is essential to treat the waste using an environmentally friendly organic oxidizing material, BIOSEL-SR2020. This study examines the effect of adding BIOSEL-SR2020 to reduce the physicochemical content of fecal sludge at the Puulonggida sludge treatment plant (STP) in Kendari City and its potential as a component of organic fertilizer. The environmental condition of Puulonggida STP shows that the air quality around the STP is excellent. The area is far from residential zones and features numerous trees, which help transform the toxic gases produced by septage treatment. The application of BIOSEL-SR2020 to septage solids significantly alters and enhances the chemical elements in the septage. Oxide composition data, such as MgO, Al2O3, SiO2, and CaO—soil components—indicate that BIOSEL-SR2020 application significantly improves chili plant growth compared to commercial organic fertilizer and untreated samples. Furthermore, treating fecal sludge liquids with BIOSEL-SR2020 affects the pH, maintaining a standard range of 7.06 - 7.13. The Dissolved Oxygen (DO) value increases slightly, and the fecal liquid’s salinity indicates no mineral salts. BIOSEL-SR2020 also demonstrates antibacterial properties, reducing bacterial colonies by an average of 26%. The most prevalent bacteria, Klebsiella sp., and Pseudomonas sp. are effective in decomposing fecal organic matter at the Puulonggida STP. In conclusion, BIOSEL-SR2020 effectively enhances the physicochemical properties of fecal sludge and holds potential as a mixture in organic fertilizers, significantly benefiting plant growth and environmental health.